Stand Density Management Diagrams for two Mediterranean pine species in Eastern Spain - Valbuena, P.; del Peso, C.; Bravo, F. (Forest Systems, 2008)
Stand Density Management Diagrams are useful tools for designing, displaying and evaluating alternative density management regimes in even-aged stands, with which to achieve a desired future stand condition. The stands studied, of Pinus halepensis and Pinus pinaster, have low productivity, and managers need easy, efficient tools to obtain the best yield. These diagrams help the managers of these stands determine thinning prescriptions. The relationship between stand density, dominant height, quadratic mean diameter and stand volume is represented in just one graph. Two equations were fitted simultaneously: one that relates quadratic mean diameter with stand density and dominant height, and another that relates total stand volume with quadratic mean diameter, stand density and dominant height.